Nitrogen‐Bridged, Natural Product Like Octahydrobenzofurans and Octahydroindoles: Scope and Mechanism of Bridge‐Forming Reductive Amination via Caged Heteroadamantanes. Issue 34 (21st August 2018) - Wales, Steven. M.; Adcock, Holly V.; Lewis, William; Hamza, Daniel; Moody, Christopher J.
Abstract : The biological significance of sp 3 ‐rich synthetic scaffolds with natural product like features yet distinct global frameworks is being increasingly recognized in medicinal chemistry and biochemistry. Taking inspiration from the vast array of bioactive, bridged alkaloids, we report the synthesis of unique, densely functionalized tricyclic scaffolds based on nitrogen‐bridged octahydrobenzofurans and octahydroindoles. These heterocycle‐rich frameworks were assembled by a one‐pot, two‐step bridge‐forming reductive amination process, which was shown to proceed via caged, heteroadamantane intermediates that thermodynamically drive an exo – endo epimerization, enabling intramolecular aza‐Michael addition over the concave face of the fused bicyclic precursors. In addition to evaluating the scope of this aza‐bridge‐forming reaction, further stereochemical complexity was introduced by subsequent diastereoselective ketone reductions and other manipulations. Finally, strategic diversity points (amino, carboxy) were decorated with common medicinal chemistry fragments, providing a set of exemplar derivatives with Lipinski‐compliant physicochemical properties. Abstract : Aza‐bridged, densely functionalized, tricyclic scaffolds based on octahydrobenzofurans and octahydroindoles have been prepared. The frameworks were assembled by a one‐pot, two‐step bridge‐forming reductive amination process, which was shown to proceed via caged, heteroadamantane intermediates that thermodynamically drive an exo – endo epimerization, enabling intramolecular aza‐Michael addition over the concave face of the fused bicyclic precursors.